Nanophase CulnS(2) nanosheets/CuS composite grown by the SILAR method leads to high performance as a counter electrode in dye sensitized solar cells - Bhosale, Reshma K.; Agarkar, Shruti A.; Agrawal, Ishita; Naphade, Rounak A.; Ogale, Satishchandra (RSC Advances, 2014)
Single phase CulnS(2) (CIS) nanosheets are synthesized on TiO2 coated FTO by the simple technique of Successive Ionic Layer Adsorption Reaction (SILAR) followed by annealing at 500 degrees C. Annealing at a lower temperature of 250 degrees C is found to yield CuS nanoparticles in addition to the CIS phase. Both single phase CIS and the CuS/CIS nanocomposite were examined as counter electrodes for a dye-sensitized solar cell (DSSC). The CIS-CuS composite is found to have a synergistic effect on the catalytic performance toward the reduction of tri-iodide, yielding a power conversion efficiency of 6.3% as compared to pristine CIS (5%) or CuS (3.5%). The possible reasons behind the high performance of the composite are elucidated using cyclic voltammetry (CV) measurements and electrochemical impedance spectroscopy (EIS).

Plasmonic light harvesting of dye sensitized solar cells by Au-nanoparticle loaded TiO2 nanofibers - Naphade, Rounak A.; Tathavadekar, Mukta; Jog, Jyoti P.; Agarkar, Shruti; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
We report a significant enhancement in the performance of dye sensitized solar cells by using in situ Au nanoparticle (Au NP) loaded TiO2 nanofibers (Au: TiO2 NFs) as the light harvesting (LH) layer as compared to the use of only TiO2 nanofibers (NFs) as the LH layer. The Au NP: TiO2 nanofibers are prepared by electro-spinning of a precursor mixture whereby nanostructured porous TiO2 nanofibers are formed and get in situ loaded with only 4-5 nm AuNPs. The as-synthesized nanofibers are characterized by X-ray diffraction, Raman, photoluminescence (PL) and Mott-Schottky analyses. The presence of gold nanoparticles shows considerable improvements in light harvesting and the electrochemical properties of TiO2 nanofibers. A remarkable enhancement in the efficiency by 25% is achieved with the AuNF LH layer as compared to 12% with the NF layer, over the value without any light harvesting layer. The IPCE and impedance analyses reveal commensurate improvements. The impedance study shows a decrease in the transport resistance (R-TiO2) and an increment in the chemical capacitance and life time of the solar cell. Systematic analyses of the optical properties suggest that the enhanced light harvesting by Au NP loaded TiO2 nanofibers is caused by the role of plasmon-polariton modes at the distributed nanoscale Schottky junctions in the Au: TiO2 nanofibers.

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets

High quality hybrid perovskite semiconductor thin films with remarkably enhanced luminescence and defect suppression via quaternary alkyl ammonium salt based treatment - Naphade, Rounak A.; Zhao, Baodan; Richter, Johannes M.; Booker, Edward; Krishnamurthy, Shrreya; Friend, Richard H.; Sadhanala, Aditya; Ogale, Satishchandra B. (Advanced Materials Interfaces, 2017)
Significant enhancement in the luminescence and superior photophysical properties of CH3NH3PbBr3 thin films prepared via simple single step spin coating process involving a novel additive mediated solvent extraction step is reported. This process results in significantly lower disorder in CH3NH3PbBr3 perovskites with Urbach energies reducing from ≈35 to ≈17 meV, which is the lowest reported value to date. The additive mediated process also results in a remarkable improvement in the photoluminescence quantum yields (PLQYs) from 1% to 30%. Coupled with the overall increase in surface roughness, a significant increase in the internal PLQY from 7% to 77% is estimated, indicating the superior quality of the treated thin films. The resultant high quality CH3NH3PbBr3 perovskites with remarkable photophysical properties can be used in realizing highly efficient optoelectronic devices. Highly efficient light emitting diodes using these perovskites are demonstrated here.